2021
DOI: 10.1002/cnma.202100388
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Capacitive Supercapacitor Derived from Self‐Oxygen Doped Biomass‐Based 3D Porous Carbon Sources

Abstract: This study reported an ultrahigh specific capacitance of a supercapacitor, using self‐oxygen doped 3D‐porous carbon derivatives from dried banana leaves. The samples were synthesized by ZnCl2 impregnation at different temperature pyrolysis of 700–900 °C. Furthermore, the overall process significantly increased the specific surface area from 429.6 to 860.4 m2 g−1 followed by the formation of 3D‐interconnected pores structures. Unexpectedly, the activated carbon demonstrated high‐level oxygen dopants between 9.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 84 publications
2
11
0
Order By: Relevance
“…However, the KOH electrolyte appeared a GCD curve that contained the greatest ion degradation characterized by a charging time, which is significantly different from the discharging time. This is closely related to oxygen heteroatoms with the potential of the evolution of O 2 and H 2 in aqueous electrolyte systems . It was also discovered that the iR drop was relatively very low, confirming the high conductivity properties of the MOLs750 precursor as summarized in Table .…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…However, the KOH electrolyte appeared a GCD curve that contained the greatest ion degradation characterized by a charging time, which is significantly different from the discharging time. This is closely related to oxygen heteroatoms with the potential of the evolution of O 2 and H 2 in aqueous electrolyte systems . It was also discovered that the iR drop was relatively very low, confirming the high conductivity properties of the MOLs750 precursor as summarized in Table .…”
Section: Resultssupporting
confidence: 55%
“…This is confirmed similarly to the previous study. 31,60 Moreover, the higher scan rate also confirms the performance of the capacitive properties of carbon MOLs as shown in Figure 5f. The scan rate treatment of 1 to 10 mV s −1 significantly reduced the specific capacitance caused by their pore size distribution.…”
Section: Table 2 Porosity Properties Of Molssupporting
confidence: 62%
See 2 more Smart Citations
“…The results showed that when the mass ratio of pinecone to ZnCl 2 was 1:4 under the pyrolysis temperature of 600 °C, the specific surface area, pore volume and mesoporosity were up to 1703 m 2 /g, 1.86 cm 3 /g and 90.1%, which enhanced 2.58, 6.91 and 3.66 times compared with that not treated with activation, respectively. Taer et al [ 121 ] studied the pyrolysis temperature impact on the activation effect of banana leaves. According to Figure 13 d–f, it could found that banana leaves-derived carbon had a more superior pore structure at the pyrolysis temperature of 800 °C (66.6%) and 900 °C (67.4%).…”
Section: Pore Size Regulation Methodsmentioning
confidence: 99%